Diagnosis of ehrlichiosis and anaplasmosis in fila brasileiro dog - Usrina, Nora; Zulkifli, Baidillah; Hidayat, Farah Amalia; Daniel, Daniel; Nurliana, Nurliana; Roslizawaty, Roslizawaty; Athaillah, Farida; Yusriani, Yenni (The International Journal of Tropical Veterinary and Biomedical Research, 2025)
Background and Aim: Canine ehrlichiosis and anaplasmosis are significant tick-borne diseases with global distribution and high clinical relevance in veterinary medicine. This case report presents a ten-year-old male Fila Brasileiro dog exhibiting clinical signs of anorexia and lethargy for three consecutive days.Materials and Methods: Physical examination revealed fever (40.3 C), pale mucous membranes, and a body condition score of 3/5. A complete blood count (CBC) showed leukocytosis, neutrophilia, eosinophilia, microcytic anemia, and thrombocytopenia. Further confirmation using a SNAP 4Dx rapid test detected antibodies against Ehrlichia spp. and Anaplasma spp., leading to a definitive diagnosis of ehrlichiosis and anaplasmosis. Treatment involved fluid therapy using intravenous 0.9% sodium chloride and doxycycline at a dose of 250 mg per day for 21 days.Results : The hematological findings align with typical abnormalities observed in dogs with these infections, including reduced erythrocyte and platelet counts, which are associated with immune-mediated destruction and bone marrow suppression. These pathogens also alter neutrophil function to evade the host immune response, contributing to prolonged inflammation and disease progression. The hematological profile presented here demonstrates a rare combination of microcytic anemia and eosinophilia, which may suggest an atypical host immune response not commonly described in previous literature.Conclusion: This case highlights the importance of early diagnosis through hematological and serological examinations and emphasizes the need for routine tick prevention to reduce the risk of tick-borne diseases in dogs.